Effects of Deficits in the Neuromuscular and Mechanical Properties of the Quadriceps and Hamstrings on Single-Leg Hop Performance and Dynamic Knee Stability in Patients After Anterior Cruciate Ligament Reconstruction. Issue 1 (31st December 2021) - He, Xin; Qiu, Jihong; Cao, Mingde; Ho, Yui Chung; Leong, Hio Teng; Fu, Sai-Chuen; Ong, Michael Tim-Yun; Fong, Daniel T.P.; Yung, Patrick Shu-Hang
Background: Understanding the role of neuromuscular and mechanical muscle properties in knee functional performance and dynamic knee stability after anterior cruciate ligament reconstruction (ACLR) may help in the development of more focused rehabilitation programs. Purpose: To compare the involved and uninvolved limbs of patients after ACLR in terms of muscle strength, passive muscle stiffness, muscle activation of the quadriceps and hamstrings, hop performance, and dynamic knee stability and to investigate the association of neuromuscular and mechanical muscle properties with hop performance and dynamic knee stability. Study Design: Cross-sectional study; Level of evidence, 3. Method: The authors studied the quadriceps and hamstring muscles in 30 male patients (mean ± SD age, 25.4 ± 4.1 years) who had undergone unilateral ACLR. Muscle strength was measured using isokinetic testing at 60 and 180 deg/s. Passive muscle stiffness was quantified using ultrasound shear wave elastography. Muscle activation was evaluated via electromyographic (EMG) activity. Hop performance was evaluated via a single-leg hop test, and dynamic knee stability was evaluated via 3-dimensional knee movements during the landing phase of the hop test. Results: Compared with the uninvolved limb, the involved limb exhibited decreased peak torque and shear modulus in both the quadriceps and hamstrings as well as delayed activity onset in the quadriceps ( P < .05 for all). The involved limb also exhibited a shorter hop distance and decreased peak knee flexion angle during landing ( P < .05 for both). Decreased peak quadriceps torque at 180 deg/s, the shear modulus of the semitendinosus, and the reactive EMG activity amplitude of the semimembranosus were all associated with shorter hop distance ( R 2 = 0.565; P < .001). Decreased quadriceps peak torque at 60 deg/s and shear modulus of the vastus medialis were both associated with smaller peak knee flexion angle ( R 2 = 0.319; P < .001). Conclusion: In addition to muscle strength deficits, deficits in passive muscle stiffness and muscle activation of the quadriceps and hamstrings were important contributors to poor single-leg hop performance and dynamic knee stability during landing. Further investigations should include a rehabilitation program that normalizes muscle stiffness and activation patterns during landing, thus improving knee functional performance and dynamic knee stability.